Improving health literacy in rural Africa through mobile phones: a systematic literature review - Ismaila, Oudraogo; SOME , Borlli Michel Jonas; BENEDIKTER, Roland; DIALLO , Gayo (Journal of Health Informatics in Africa, 2022)
Background and Purpose: Mobile phones have been used to support healthcare systems through various mobile health (m-health) applications. In Africa, m-health initiatives have been used in many interventions, including education and awareness, clinical and non-clinical decision support systems, epidemic outbreak tracking, training of healthcare workers and remote monitoring, and many others. But despite the great enthusiasm around m-health, few studies have examined the use of mobile phones to improving health literacy in rural areas in Africa. Methods: We performed a literature review using SCOPUS and Google scholar, combined with manual searching methods to search for studies related to m-health initiatives in Africa. The systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) protocol. Four steps were followed to identify relevant publications related to the contribution of mobile technologies in improving health literacy :(1) Database selection (2) Keyword search, (3) Study selection and (4) Data extraction. Results: In our study, we found 5 studies related to health literacy and mobile technologies in Africa. However, none of them were focused on health literacy and mobile technologies in rural areas of Africa. This result provides insights of future studies to conduct. Conclusions: We found that m-health initiatives were so far not inclusive. It appears that few m-health solutions integrate local languages in the development of m-health solution. The mhealth initiatives need to be implemented based on the local realities, so experimental studies are desired to test the adaptability of mhealth projects and to explore any adjustments required.